The influence of sentence elicitation variables on children's speech production. - Weston AD (Journal of Speech, Language & Hearing Research, 1997)
This study investigated the potential influence of adult-modeled sentences on the speech production of 15 children with speech delays of unknown origin. Two comparison tokens of target words containing sounds with inconsistently realized phonemes were sampled in picture descriptions elicited with and without adult-modeled descriptive sentences. Ten listeners made forced-choice paired-comparisons to identify the children's relatively more advanced word productions. From 205 total comparisons, listeners identified 130 word pairs that included one token more advanced than the other. Significantly more of the children's advanced word productions occurred in sentences elicited with an adult model sentence. Discussion considers theoretical and clinical perspectives of an assumption that variables facilitating children's language production may benefit speech production.